Identifying code-mixed and code-switched hateful remarks on social media using NLP - Sinha, Sumaiya; Nawar, Naharin Siddiqui; Khan, Md. Abrar Faiaz (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2024.